Antifungal Activity of Plasmacytoid Dendritic Cells and the Impact of Chronic HIV Infection - Maldonado, Samuel; Fitzgerald-Bocarsly, Patricia (Frontiers in Immunology, 2017)
Due to the effectiveness of combined antiretroviral therapy, people living with HIV can control viral replication and live longer lifespans than ever. However, HIV-positive individuals still face challenges to their health and well-being, including dysregulation of the immune system resulting from years of chronic immune activation, as well as opportunistic infections from pathogenic fungi. This review focuses on one of the key players in HIV immunology, the plasmacytoid dendritic cell (pDC), which links the innate and adaptive immune response and is notable for being the body’s most potent producer of type-I interferons (IFN). During chronic HIV infection, the pDC compartment is greatly dysregulated, experiencing a substantial depletion in number and compromise in function. This immune dysregulation may leave patients further susceptible to opportunistic infections. This is especially important when considering a new role for pDCs currently emerging in the literature: in addition to their role in antiviral immunity, recent studies suggest that pDCs also play an important role in antifungal immunity. Supporting this new role, pDCs express C-type lectin receptors (CLR) including dectin-1, dectin-2, dectin-3, and mannose receptor, and Toll-like receptors (TLR) -4 and -9 that are involved in recognition, signaling, and response to a wide variety of fungal pathogens, including Aspergillus fumigatus, Cryptococcus neoformans, Candida albicans, and Pneumocystis jirovecii. Accordingly, pDCs have been demonstrated to recognize and respond to certain pathogenic fungi, measured via activation, cytokine production, and fungistatic activity in vitro, while in vivo mouse models indicated a strikingly vital role for pDCs in survival against pulmonary Aspergillus challenge. Here, we discuss the role of the pDC compartment and the dysregulation it undergoes during chronic HIV infection, as well as what is known so far about the role and mechanisms of pDC antifungal activity.